Assessing the Total Levels and Health Risk of Presence of Cadmium, Cobalt, Copper, Lead and Zinc in Most Smoked Tobacco Sold in Alassaba Municipality-Libya - Salem Irhema S. Irhema; Adel Almaprok S. Arhouma; Sarah Abdulhakim Al-Shaqlouf; Fatima Aboulqasim Haba (African Journal of Advanced Pure and Applied Sciences, 2024)
Tobacco is one of the sources that may introduce several heavy metals into the bodies of positive and negative smokers, leading to harmful effects on smokers’ bodies. Because a major number of Libyan populations are smoking different brands of cigarettes alongside raw tobacco leaves which may affect our citizens’ health, accordingly 10 cigarette brands comprising Bon International, Gold Mexico Original, Camel Yellow, D&G, Milano London, Milano, Oris Fliter. Karelia Ligts, Yes and Libyan brand named Ryadi, and another sample of raw tobacco leaves (LRT) planted locally were collected randomly from local shops distributed in Alassaba municipality with aims to determine the total concentration of Cadmium (Cd), Cobalt (Co), Copper (Cu), Lead (Pb) and Zinc (Zn) and calculate the health risk related to the presence of these metals in the most consumed tobacco. The obtained results showed that all collected tobacco samples contained various levels of Cd, Co, Cu Pb and Zn (mg/kg) ranged from 0.38 ± 0.07 to 0.84 ± 0.01, 0.33 ± 0.04 to 0.5 ± 0.07, 15.29 ± 0.88 to 18.75 ± 0.72, 0.42 ± 0.04 to 1.04 ± 0.11 and 14.33 ± 0.33 to 32.45 ± 2.09, respectively. The mean levels of Co, Cu and Zn were within the allowable levels set by the World Health Organization (WHO), whereas Pb and Cd levels were above the acceptable levels. The calculated harm quotient (HQ) of target metals were greater than 1 representing extreme health risk due to the presence of Cd, Cu Pb and Zn in studied tobacco, nevertheless, the HQ of Co were lower than 1 presenting minimal health risk to the smokers. In conclusion, there is a need to emphasize the regulation of the import and tread of tobacco and monitor the content of heavy metals in tobacco to reduce the health effects of these cigarette brands.